Update on Prevalence of Periodontitis in Adults in the United States: NHANES 2009 to 2012. Issue 5 (1st May 2015) - Eke, Paul I.; Dye, Bruce A.; Wei, Liang; Slade, Gary D.; Thornton‐Evans, Gina O.; Borgnakke, Wenche S.; Taylor, George W.; Page, Roy C.; Beck, James D.; Genco, Robert J.
Abstract : Background: This report describes prevalence, severity, and extent of periodontitis in the US adult population using combined data from the 2009 to 2010 and 2011 to 2012 cycles of the National Health and Nutrition Examination Survey (NHANES). Methods: Estimates were derived for dentate adults, aged ≥30 years, from the US civilian non‐institutionalized population. Periodontitis was defined by combinations of clinical attachment loss (AL) and periodontal probing depth (PD) from six sites per tooth on all teeth, except third molars, using standard surveillance case definitions. For the first time in NHANES history, sufficient numbers of non‐Hispanic Asians were sampled in 2011 to 2012 to provide reliable estimates of their periodontitis prevalence. Results: In 2009 to 2012, 46% of US adults, representing 64.7 million people, had periodontitis, with 8.9% having severe periodontitis. Overall, 3.8% of all periodontal sites (10.6% of all teeth) had PD ≥4 mm, and 19.3% of sites (37.4% teeth) had AL ≥3 mm. Periodontitis prevalence was positively associated with increasing age and was higher among males. Periodontitis prevalence was highest in Hispanics (63.5%) and non‐Hispanic blacks (59.1%), followed by non‐Hispanic Asian Americans (50.0%), and lowest in non‐Hispanic whites (40.8%). Prevalence varied two‐fold between the lowest and highest levels of socioeconomic status, whether defined by poverty or education. Conclusions: This study confirms a high prevalence of periodontitis in US adults aged ≥30 years, with almost fifty‐percent affected. The prevalence was greater in non‐Hispanic Asians than non‐Hispanic whites, although lower than other minorities. The distribution provides valuable information for population‐based action to prevent or manage periodontitis in US adults.